The Idea of Atonement in the Philosophy of Hermann Cohen - Zank, Michael (Brown Judaic Studies, 2020)
In The Idea of Atonement in the Philosophy of Hermann Cohen (2000), Michael Zank argues that the idea of atonement serves as a key for understanding the larger philosophy of the German-Jewish philosopher Hermann Cohen (1842-1918). Zank situates his sensitive and wide-ranging philosophical evaluation of Cohen within the intellectual and social milieu within which Cohen wrote. The book contains a new preface by the author.